2010
DOI: 10.1364/ol.35.003685
|View full text |Cite
|
Sign up to set email alerts
|

On the higher-order Kerr effect in femtosecond filaments

Abstract: A recent experiment probing the electronic nonlinearity in the femtosecond filament indicated that the optical Kerr effect not only saturates but even changes its sign at high intensities and thus switches from self-focusing to a strongly defocusing regime. Here we examine, through simulations and experiment, some implications of such a behavior. We perform comparative simulations based on the standard model on one hand and on a model implementing the intensity-dependent Kerr effect on the other. Comparison wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 10 publications
2
34
0
Order By: Relevance
“…[37][38][39][40][41]) will reduce the need to assumeg an initial field with no spatiotemporal dependences or to use apertured FROG traces. Additionally, recent investigations into the possible role of high-order nonlinear optical effects [42][43][44], ionization by multichromatic pulses [45], and the influence of phenomenological parameters (such as the free-carrier collision time and the effective electron mass) [46] may also allow for further improvements in predamage calculations.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39][40][41]) will reduce the need to assumeg an initial field with no spatiotemporal dependences or to use apertured FROG traces. Additionally, recent investigations into the possible role of high-order nonlinear optical effects [42][43][44], ionization by multichromatic pulses [45], and the influence of phenomenological parameters (such as the free-carrier collision time and the effective electron mass) [46] may also allow for further improvements in predamage calculations.…”
Section: Discussionmentioning
confidence: 99%
“…It would overturn the picture most have of the mechanism behind long-range filamentary propagation of intense ultrashort pulses -as arising from an interplay between self-focusing due to the positive optical nonlinearity from bound electrons and defocusing due to the plasma generated by ionization. The existence of a higher-order Kerr effect would also have implications for the general nonlinear susceptibility in transparent media [7,8], including harmonic generation [9][10][11].Subsequent experimental studies of light filaments [12][13][14][15] have not supported the higher-order Kerr model, with one exception [16]. One measurement [13] found that the electron density was two orders of magnitude higher than predicted by a calculation including higher-order nonlinearities, but agreed with a simulation based on plasma defocusing alone [5].…”
mentioning
confidence: 99%
“…As a consequence, the HOKE can ensure self-defocusing in filaments and balance Kerr self-focusing [10], in place of the plasma, especially for short pulses [9]. This result raised an active controversy [11][12][13][14][15][16] in the lack of direct experimental confirmation.…”
mentioning
confidence: 99%